A national analysis of trends, outcomes and volume–outcome relationships in thyroid surgery. (14th September 2016) - Nouraei, S.A.R.; Virk, J.S.; Middleton, S.E.; Aylin, P.; Mace, A.; Vaz, F.; Kaddour, H.; Darzi, A.; Tolley, N.S.
Abstract : Objectives: Thyroid conditions are common, and their incidence is increasing. Surgery is the mainstay treatment for many thyroid conditions, and understanding its utilisation trends and morbidity is central to improving patient care. Design: An N = near‐all analysis of the English administrative dataset to identify trends in thyroid surgery specialisation, volume–outcome relationships, and the incidence and risk factors for short‐ and long‐term morbidity. Main outcome measures: Between 2004 and 2012, 72 594 patients underwent elective thyroidectomy in England. Information about age, sex, morbidities, nature of thyroid disease and surgery, adjuvant treatments and complications including hypocalcaemia and vocal palsy was recorded. Results: Mean age at surgery was 49 ± 30, and a female predominance (82%) was observed. Most patients underwent hemithyroidectomy (51%) or total thyroidectomy (32%). Patients underwent surgery for benign (52.5%), benign inflammatory (21%) and malignant (17%) thyroid diseases. Thyroid surgery grew by 2.9% a year and increased in specialisation. Increased surgeon volume significantly reduced lengths of stay: the proportion of length of stay outliers fell from 11.8% for patients of occasional thyroidectomists (<5 per year) to 2.8% for patients of high‐volume surgeons (>50 thyroidectomies a year). Post‐discharge vocal palsy and hypocalcaemia occurred in 1.87% and 1.58% of cases, respectively. High‐volume surgeons had a reduced incidence of vocal palsy, and volumes >30 were consistently protective. Conclusions: Thyroid surgery is increasingly specialised. High‐volume surgeons, that is patients who perform 50 or more thyroidectomies per year, achieve lower complications and shorter lengths of stay.